Enhancing renewable energy integration through energy storage and smart grid innovations: A systematic review - Kaseem A. Obakhume; Faith F. Opatola (BIORE Scientia Academy, 2025)
This study presents a systematic review of advancements in energy storage technologies and intelligent grid management systems and evaluates their combined role in enhancing the reliability, efficiency, and integration of renewable energy sources. A comprehensive search across major databases identified 170 records, of which nine studies met PRISMA-based inclusion criteria after rigorous screening. The findings indicate that energy storage technologies, particularly lithium-ion batteries, pumped hydro storage, and emerging hybrid systems, significantly improve grid stability by mitigating renewable intermittency, supporting load balancing, and optimizing charge–discharge cycles through advanced scheduling techniques. Parallel innovations in smart grid technologies, including advanced metering infrastructure, demand response mechanisms, enhanced forecasting tools, and communication-enabled automation, strengthen real-time system flexibility and reduce operational stress associated with fluctuating renewable output. Integrated approaches, especially Virtual Power Plants that aggregate distributed energy resources, demonstrate superior performance by enabling coordinated dispatch, improving system resilience, and supporting higher levels of renewable penetration. Despite these benefits, challenges such as high capital costs, uneven technological readiness, regulatory gaps, and cybersecurity vulnerabilities persist. Overall, the review underscores that the convergence of advanced storage technologies with digitally optimized grid architectures is essential to achieving stable, efficient, and low-carbon electricity systems capable of supporting global decarbonization goals.